PENGARUH LITERASI KEUANGAN DAN PENGELOLAAN KEUANGAN TERHADAP LAPORAN KEUANGAN UMKM KAMPUNG KUE RUNGKUT LOR SURABAYA - Fitria Angelina; Ratih Dewi Titisari Haryana (LPPM STIE Muhammadiah Bandung, 2025)
Financial management is the most important task for business actors, especially micro-economic actors who often operate at the MSME level. To run their business, business actors must have financial literacy. The purpose of this study is